Failing to learn or learning to fail? A meta-analysis of evaluations of gender in Ethiopian agricultural development - Springer, Emily (University of Minnesota, 2019)
Presented by Emily Springer (University of Minnesota) on February 28, 2019, as part of the webinar 'Changing gender norms in agriculture projects - What works in Pakistan and Ethiopia'. The webinar was co-organized by the CGIAR Collaborative Platform for Gender Research and the CGIAR Research Program on WHEAT.